Pengaruh Promosi Live Streaming Tiktok dan Harga terhadap Minat Beli Pada Skincare Skintific - Azalia, Hayyu Puri; Abdurrahman, Agus (SAFE-Network, 2025)
This research aims to explore the practice of implementing social media strategies by companies, especially in the context of product promotion through social media platforms such as live streaming and providing discounts. The main focus of the research is on efforts to increase customer buying interest, especially on the TikTok platform, using Skintific products as a case study. The method used is a quantitative approach by distributing questionnaires to 250 respondents. The research results show that there is a significant relationship between the use of live streaming, giving discounts, and customer purchasing interest. These findings highlight the importance of an integrated social media strategy in increasing customer engagement and supporting business growth. The main conclusion of this research is that the use of social media strategies such as live streaming and promotional offers can positively influence customer purchasing interest on the TikTok platform, providing valuable insights for companies in designing effective marketing strategies in today's digital era.